2018
DOI: 10.1177/0009922818759320
|View full text |Cite
|
Sign up to set email alerts
|

Vital Signs as Predictor Factors of Intravenous Immunoglobulin Resistance in Patients With Kawasaki Disease

Abstract: Kawasaki disease (KD) is the most common cause of acquired heart disease in children. Intravenous immunoglobulin (IVIG) may significantly lower the frequency of coronary artery complications. However, some patients do not respond to initial therapy and are at higher risk of developing coronary artery lesion. A retrospective analysis of data from 419 KD patients was performed. The patients were divided into IVIG responders (n = 318) and IVIG nonresponders (n = 101). Multivariate logistic regression analysis rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
(34 reference statements)
0
7
0
1
Order By: Relevance
“…In 1 previous study, a temperature .38.8°C was used before IVIg infusion in the predictive model; however, the authors defined IVIg nonresponse as a temperature $37.5°C within 48 hours of IVIg treatment start, which may overestimate the rate of nonresponse. 10 Antipyretic IVIg premedication at our institution limited the utility of pre-IVIg temperatures in our population. Canadian researchers found significant differences in temperature patterns after IVIg treatment in patients by level of nonresponse (complete or partial nonresponse versus complete response), 35 supporting our findings.…”
Section: Results From Each Sensitivity Analysis (Supplementalmentioning
confidence: 97%
See 2 more Smart Citations
“…In 1 previous study, a temperature .38.8°C was used before IVIg infusion in the predictive model; however, the authors defined IVIg nonresponse as a temperature $37.5°C within 48 hours of IVIg treatment start, which may overestimate the rate of nonresponse. 10 Antipyretic IVIg premedication at our institution limited the utility of pre-IVIg temperatures in our population. Canadian researchers found significant differences in temperature patterns after IVIg treatment in patients by level of nonresponse (complete or partial nonresponse versus complete response), 35 supporting our findings.…”
Section: Results From Each Sensitivity Analysis (Supplementalmentioning
confidence: 97%
“…For example, in many studies, IVIg nonresponse is defined as a temperature $37.5°C, which is below the typical US threshold of 38.0°C to 38.5°C. 5,6,9,10,12 This difference may lead to an overestimation of nonresponse and limits applicability of risk prediction models to US patients.…”
Section: Results From Each Sensitivity Analysis (Supplementalmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, finding biomarkers that can predict IVIG resistance is an important area of current KD research. Neutrophils [14,[77][78][79][80][81], B cells [23], CD8+ T cells [82], and Th17 cells [32,33] in KD peripheral blood have all been reported to predict IVIG resistance, but the types of immune cells supported by different studies are not consistent. Our research did not identify immune cells that can accurately predict IVIG response in multiple datasets.…”
Section: Discussionmentioning
confidence: 99%
“…18 Five studies reported that patients with poorly documented or unclassified clinical data during hospitalization were excluded. 17,[25][26][27][28] (Supplementary Table 2).…”
Section: Characteristics Of the Modelsmentioning
confidence: 99%